Copepod Grazing Influences Diatom Aggregation and Particle Dynamics - Toullec, Jordan; Vincent, Dorothée; Frohn, Laura; Miner, Philippe; Le Goff, Manon; Devesa, Jérémy; Moriceau, Brivaëla (Frontiers in Marine Science, 2019)
Carbon export is driven by particle flux which is modulated by aggregation, remineralisation and grazing processes. Zooplankton contribute to the sinking flux through the egestion of fast sinking faecal pellets but may also attenuate the flux by tearing apart phytoplankton aggregates into small pieces. Freely suspended cells, artificial monospecific aggregates from two different diatom species (Chaetoceros neogracile and Skeletonema marinoi) and natural aggregates of Melosira sp. were independently incubated with five different copepod species (Acartia clausi, Temora longicornis, Calanus helgolandicus, Euterpina acutifrons and Calanus hyperboreus). During the grazing experiments initiated with free diatoms, E. acutifrons feeding activity evidenced by ingestion rates of 157 ± 155 ng Chl a ind-1 d-1, induced a significant increase of S. marinoi aggregation. TEP production was only slightly boosted by the presence of grazers and turbulences created by swimming may be the main trigger of the aggregation processes. All copepods studied were able to graze on aggregates and quantitative estimates led to chlorophyll a ingestion rates (expressed in Chla a equivalent, i.e. the sum of chlorophyll a and phaeopigments in their guts) ranging from 4 to 23 ng Chl aeq ind-1 d-1. Three main trends in particle dynamics could be identified and further link to the copepod feeding behaviour and the size ratio between prey and predators: 1) Fragmentation of S. marinoi aggregates by the cruise feeder T. longicornis and of Melosira sp. aggregates by C. hyperboreus at prey to predator size ratios larger than 15 ; 2) No change of particle dynamics in the presence of the detritic cruise feeder E. acutifrons; and finally 3) re-aggregation of C. neogracile and S. marinoi aggregates when the two filter feeders A. clausi and C. helgolandicus were grazing on aggregate at prey to predator size ratios lower than 10. Aggregation of freely suspended cells or small aggregates was facilitated by turbulence resulting from active swimming of small copepods. However, stronger turbulence created by larger cruise feeders copepods prevent aggregate formation and even made them vulnerable to breakage.